(untitled) (Baghdad Science Journal, 2011)
We studied in this research how to find a method of estimating the quantity (Kinetically) of three kinds of Insecticide and their mixture, which are used in agriculture. The extracted insecticide from the polluted samples with these insect from air, soil, and the leaves of trees, have be used into the reaction with H2O2 and benzedine. The kinetic study of this reaction was formed in basic medium,( pH= 8.6), using UV. Spectra at (?= 420nm). The study showed that the reaction is the first order, and the speed of the reaction was used to estimate the concentration of insecticide in solution and mixture. The experiments of this study indicated that this method has the speed and efficiency for quantitatively estimating these insecticides in solution and mixture.